EFEKTIVITAS KEBIJAKAN "MERDEKA BELAJAR, KAMPUS MERDEKA" BAGI MAHASISWA DI DAERAH PERBATASAN - Dimmera, Bella Ghia; Lumbantobing, Winda Lidia; Purnasari, Pebria Dheni; Sadewo, Yosua Damas; Saputro, Totok Victor Didik (NOKEN : Jurnal Pengelolaan Pendidikan, 2023)
The purpose of this study is to determine the effectiveness of the "Merdeka Belajar, Kampus Merdeka" (MBKM) policy for students in border areas. The problems that exist in border areas are analyzed through descriptive qualitative case studies. The main data sources for this research were obtained through surveys and interviews. Questionnaires and instructions for surveys were given to respondents, namely students. Data were collected through interviews and documentation; triangulation to ensure data validity; and data were analyzed through reduction, presentation, and conclusion drawing. The results of the study revealed that the target of the MBKM policy for 36 students is the effectiveness of the MBKM policy in border areas is considered not entirely appropriate.Â  The results obtained are not the right policy, not the right implementation, not the right target, and not the right environment.Â  With the existence of the MBKM policy, students have not received and understood the benefits, namely the MBKM policy has been socialized but students have not understood it well, not yet appropriate implementation, that the government has established the MBKM policy, but it is not in accordance with the conditions of universities in border areas. Not yet on target, that education equity has not yet reached the target. Not yet appropriate environment, that the MBKM policy has not provided information related to educational development in border areas.